Temporal variations in the triggering of myocardial infarction by air temperature in Augsburg, Germany, 1987-2014 - Chen, Kai; Breitner, Susanne; Wolf, Kathrin; Hampel, Regina; Meisinger, Christa; Heier, Margit; von Scheidt, Wolfgang; Kuch, Bernhard; Peters, Annette; Schneider, Alexandra (European heart journal, 2019)
The association between air temperature and mortality has been shown to vary over time, but evidence of temporal changes in the risk of myocardial infarction (MI) is lacking. We aimed to estimate the temporal variations in the association between short-term exposures to air temperature and MI in the area of Augsburg, Germany. Over a 28-years period from 1987 to 2014, a total of 27 310 cases of MI and coronary deaths were recorded. Daily meteorological parameters were measured in the study area. A time-stratified case-crossover analysis with a distributed lag non-linear model was used to estimate the risk of MI associated with air temperature. Subgroup analyses were performed to identify subpopulations with changing susceptibility to air temperature. Results showed a non-significant decline in cold-related MI risks. Heat-related MI relative risk significantly increased from 0.93 [95% confidence interval (CI): 0.78-1.12] in 1987-2000 to 1.14 (95% CI: 1.00-1.29) in 2001-14. The same trend was also observed for recurrent and non-ST-segment elevation MI events. This increasing population susceptibility to heat was more evident in patients with diabetes mellitus and hyperlipidaemia. Future studies using multicentre MI registries at different climatic, demographic, and socioeconomic settings are warranted to confirm our findings. We found evidence of rising population susceptibility to heat-related MI risk from 1987 to 2014, suggesting that exposure to heat should be considered as an environmental trigger of MI, especially under a warming climate.